Features arterial renal blood flow in acute pancreatitis - Yu. S. Vinnik; E. V. Repina; E. V. Serova; M. A. Makarkina; D. Yu. Lopatin; V. P. Pustovalov (Кубанский научный медицинский вестник, 2015)
Doppler ultrasound dynamic in interlobar arteries allows indirectly assess arterial blood flow component intraorganic, state microvasculature of kidneys when they are damaged on the background of endotoxemia, as well as state of the peripheral vascular bed of the kidney and the degree of functional disorders in acute pancreatitis. Hemodynamics indicators in renal interlobar arteries in conjunction with standard laboratory methods to help in determining the extent of kidney damage in acute pancreatitis and its destructive forms.